Aspectos psicológicos en víctimas de violencia intrafamiliar con afectación psicológica: revisión documental sobre análisis y conclusiones forenses de informes periciales psicológicos - Acosta Perez, Sandra Mireya (Universidad Antonio Nariño, 2024)
The main objective of this present degree thesis work, was to identify the psychological aspects that were found in ten psychological expert reports of victims of domestic violence who were affected, and also how the expert was supported to determine the existence of abuse, as well as to establish signs and /or symptoms that were considered in the analysis and forensic conclusions issued by the expert. In addition, considering that the domestic violence phenomenon is increasing and it is currently represented with important and recent evidenced studies by entities such as the National Institute of Legal Medicine and Forensic Sciences in Bogotá City, DC.